Fracture Healing in Patients With HIV in South Africa: A Prospective Cohort Study. (15th August 2021) - Graham, Simon M.; Maqungo, Sithombo; Laubscher, Maritz; Ferreira, Nando; Held, Michael; Harrison, William J.; Simpson, A. Hamish; MacPherson, Peter; Lalloo, David G.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: HIV reduces bone mineral density, mineralization, and turnover and may impair fracture healing. Setting: This prospective cohort study in South Africa investigated whether HIV infection was associated with impaired fracture healing after trauma. Methods: All adults with acute tibia and femur fractures who underwent intermedullary (IM) nailing for fracture fixation between September 2017 and December 2018, at 2 tertiary hospitals, were followed up for a minimum of 12 months postoperatively. The primary outcome was delayed bone union at 6 months (defined by the radiological union scoring system for the tibia score <9), and the secondary outcome was nonunion (defined as radiological union scoring system for the tibia score <9) at 9 months. Multivariable logistic regression models were constructed to investigate the associations between HIV status and impaired fracture healing. Results: In total, 358 participants, who underwent 395 IM nailings, were enrolled in the study and followed up for 12 months. Seventy-one of the 358 (19.8%) participants were HIV-positive [83/395 (21%) IM nailings]. HIV was not associated with delayed fracture healing after IM nailing of the tibia or femur (multivariable odds ratio: 1.06; 95% confidence interval: 0.50 to 2.22). HIV-positive participants had a statistically significant lower odds ratio of nonunion compared with HIV-negative participants (multivariable odds ratio: 0.17; 95% confidence interval: 0.01 to 0.92). Conclusions: Fractures sustained in HIV-positive individuals can undergo surgical fixation as effectively as those in HIV-negative individuals, with no increased risk of delayed union or nonunion.